Determination of lomefloxacin in tablet preparations by liquid chromatography - Tozo, Greci C. G. [UNESP]; Salgado, Hérida R. N. [UNESP] (My University, 2006)
A sensitive, precise, and specific high-performance liquid chromatography (HPLC) method was developed for the assay of lomefloxacin (LFLX) in raw material and tablet preparations. The method validation parameters yielded good results and included the range, linearity, precision, accuracy, specificity, and recovery. It was also found that the excipients in the commercial tablet preparation did not interfere with the assay. The HPLC separation was performed on a reversed-phase Phenomenex C18 column (150 × 4.6 mm id, 5 μ particle size) with a mobile phase composed of 1% acetic acid-acetonitrile- methanol (70 + 15 + 15, v/v/v), pumped isocratically at a flow rate of 1.0 mL/min. The effluent was monitored at 280 nm. The calibration graph for LFLX was linear from 2.0 to 7.0 mg/mL. The interday and intraday precisions (relative standard deviation) were less than 1.0%. The method was applied for the quality control of commercial LFLX tablets to quantitate the drug.